2015
DOI: 10.1177/1477370815617191
|View full text |Cite
|
Sign up to set email alerts
|

Importation and deprivation correlates of misconduct among Romanian inmates

Abstract: Correctional literature on determinants of prisoner misconduct is largely focused on the situation in the USA or West European countries. This study expands the research in this field by presenting findings from Romania, an East European country whose prison system faces severe problems, among which overcrowding and poor confinement conditions are of the utmost concern. Therefore a survey was conducted on a sample of 280 adult male inmates in four large Romanian prisons. These exceptional data were supplemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 34 publications
(44 reference statements)
2
21
0
3
Order By: Relevance
“…Citing a wide range of literature Dhami et al (2002) suggest that 'imported' factors have been shown to be better predictors of mal-adaption than indigenous factors, but they note that some 'imported' factors appear to have no predictive power. Similarly, Dâmboeanu and Nieuwbeerta (2016) found a strong relationship between a range of importation and indigenous factors and types of prison misconduct, but also reported differential impact. The testing of situational factors is less commonly reported in the literature, but Jiang and Fisher-Girolando (2002) found situational factors to be the most powerful predictor of violent incidents although the relative power differs depending on the nature of the infraction.…”
Section: Introductionmentioning
confidence: 92%
“…Citing a wide range of literature Dhami et al (2002) suggest that 'imported' factors have been shown to be better predictors of mal-adaption than indigenous factors, but they note that some 'imported' factors appear to have no predictive power. Similarly, Dâmboeanu and Nieuwbeerta (2016) found a strong relationship between a range of importation and indigenous factors and types of prison misconduct, but also reported differential impact. The testing of situational factors is less commonly reported in the literature, but Jiang and Fisher-Girolando (2002) found situational factors to be the most powerful predictor of violent incidents although the relative power differs depending on the nature of the infraction.…”
Section: Introductionmentioning
confidence: 92%
“…A large corpus of studies using prisoner data from California (Caudill et al, 2014), Kentucky, Ohio (Cao et al, 1997), Tennessee (Lahm, 2008), Oregon (Cihan et al, 2017), Texas (DeLisi et al, 2011), the federal Bureau of Prisons (Dhami et al, 2007; Walters & Crawford, 2013), and regional and national-level U.S. data (Celinska & Sung, 2014; Diamond et al, 2012; Jiang & Fisher-Giorlando, 2002; Poole & Regoli, 1983; Worrall & Morris, 2012) provide empirical support for the importation model. The viability of the importation model is not limited to an American context as empirical support also exists using data from Canada (Ruddell & Gottschall, 2011), Germany (Klatt et al, 2016), and Romania (Dâmboeanu & Nieuwbeerta, 2016).…”
Section: Theoretical Background: the Importation Model Of Inmate Behamentioning
confidence: 99%
“…Deprivation theory posits that institutional misconduct is explained by the prison environment (Dâmboeanu & Nieuwbeerta, 2016). Its proponents would evaluate prison regulations, inmate–inmate and staff–inmate interactions, and the quality and quantity of amenities when examining violations.…”
Section: Introductionmentioning
confidence: 99%